Deepfakes or Synthetic Media? The Effect of Euphemisms for Labeling Technology on Risk and Benefit Perceptions - Adrian Rauchfleisch; Daniel Vogler; Gabriele de Seta (Social Media + Society)
The language used in public debates and in the news can influence how citizens perceive the risks and benefits of technology. While framing effects on technology perception are well understood, few studies have focused on the effects of specific terms used to describe technology. We analyze how the terms deepfake and synthetic media affect risk and benefit perceptions across application fields. Using Switzerland as a case, our manual content analysis ( n  = 380 news articles) reveals a focus on risks in news coverage of deepfakes with minimal use of the term synthetic media. We then tested the effects of the terms on risk and benefit perceptions in a preregistered survey experiment (n = 736 participants). Term choice does not change perceived risks, but “synthetic media” significantly increases perceived benefits across application fields. As a theoretical contribution, we link our findings to the concept of euphemism, proposing that term choice should align with application fields to reflect the risks and benefits of technology. Overall, our study shows that the terms we use to label technology matter, especially for emerging technologies such as artificial intelligence.